CHANGES IN STEREOSCOPIC VISION TOWARDS STRABISMUS CORRECTION SURGERY IN DR MOHAMMAD HOESIN CENTER HOSPITAL, PALEMBANG: Oral Presentation - Experimental Study - Ophthalmologist - TRI KARTIKA UTOMO; dr. Linda Trisna, Sp.M, SubSp POS (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : This study aims to determine the improvement of binocular vision function after restoring the lost fusion with strabismus correction Methods : A before and after design clinical trial study was carried out at the Eye Polyclinic of the Moh. Hoesin Hospital in Palembang from June 2021 to February 2022 with a sample of 16 people. Stereoscopic vision examination was carried out with the TNO Stereo Test (Toegepast Natuurwetenschappeelijk Onderzoek) examination before and after strabismus correction was carried out. Analysis of research results with SPSS version 22.0. Results : In this study it was found that stereoscopic vision before surgery could improve significantly after strabismus correction and dichoptic training for 1 month (p<0.05) as much as 68.75%. Meanwhile, confounding factors such as the type of deviation, the magnitude of the deviation, the initial onset of the deviation and the duration of the deviation did not significantly influence the incidence of increased stereoscopic vision improvement in the study subjects (p<0.05). Conclusion : There is an increase in the value of binocular vision in strabismus patients after strabismus surgery and undergoing dichoptic vision training for 1 month. Dichoptic training can improve the function of binocular vision.